ANALGESIC POWER OF DICHLOROMETHANA EXTRACT OF SWEET POTATO LEAVES (IPOMOEA BATATAS L) IN MICE - Hastuti, Siwi (LPPM Universitas Duta Bangsa Surakarta, 2025)
Sweet potato (Ipomoea batatas L) contains flavonoids, polyphenols and saponins. Sweet potato leaves have been empirically used as a medicine for boils, wounds and as a medicine for reducing fever. This study aims to determine the analgesic power of dichloromethane extract of sweet potato leaves in mice induced by chemical stimuli. Simplicia extraction was carried out by maceration with dichloromethane. The test groups were group I (Acetosal 65 mg/kgBW), group II (coconut oil as negative control), groups III, IV and V (dichloromethane extract of sweet potato leaves at doses of 100, 200 and 400 mg/ kgBB). Each group was given the test preparation orally, then immediately injected 1% acetic acid intraperitoneally. The mice's movements were recorded every five minutes for one hour. The number of writhes is used to calculate the percentage of analgesic power. The results of the percentage of analgesic power of the test preparations at doses of 100, 200 and 400 mg/kgBW were (13.48 ± 2.00)%, (49.33 ± 1.59)% and (57.92 ± 1.63 )%, while acetosal has an anagetic power percentage of (59.99 ± 0.04)%. The results of the one way Anova test show a significance value of 0.000, meaning there was a significant difference. However, in the post hoc test, the test treatments showed significant differences except between the test dosage preparation of 400 mg/kgBW and acetosal. Sweet potato leaves have the potential to be used as a new analgesic medicine.